2022
DOI: 10.1155/2022/1026698
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat Transfer from Convective and Radiative Stretching/Shrinking Rectangular Fins

Abstract: We study the efficiency of shrinking/stretching radiative fins to improve heat transfer rate. To evaluate the competence of suggested fins, the influence of shrinking/stretching, thermogeometric parameters, surface temperature, convection conduction, radiation conduction, and Peclet number is investigated. The problem is solved numerically using a shooting method. To validate the numerical solution, the results are compared with the solution of a differential transform method. Temperature distribution increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition, various parameters are compared with the literature. 17,35,50 It has been observed that the temperature profile of the rectangular and trapezoidal fins decreases as Hartmann number, convection, and radiation parameters increase, but increases as internal heat generation, Peclet number, and ambient temperature parameters decrease. The present work in Figures 2-4 also shows a similar result for trapezoidal and rectangular fins under the effect of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, various parameters are compared with the literature. 17,35,50 It has been observed that the temperature profile of the rectangular and trapezoidal fins decreases as Hartmann number, convection, and radiation parameters increase, but increases as internal heat generation, Peclet number, and ambient temperature parameters decrease. The present work in Figures 2-4 also shows a similar result for trapezoidal and rectangular fins under the effect of the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the different parameters were shown to verify the results obtained in this manuscript. The numerical illustration of the BVPs investigated that the existence and uniqueness results with Ulam stability comprise one of the challenging tasks to investigate for such problems [32][33][34][35][36][37]. The physical systems in the fields of plasma physics, electrical engineering, and biological models, hybrid fractional sequential integro-differential equations (HFSID) play a key role due to their double-fractional-order derivative.…”
Section: Discussionmentioning
confidence: 99%
“…They have derived exact solutions for the tip temperature and efficiency of pin fin structures as well. In a recent analysis, the stretching/shrinking longitudinal fin structures subject to convective‐radiative heat exchange were analyzed by Din et al 9 The differential transform method (DTM) was employed by them for the analysis.…”
Section: Introductionmentioning
confidence: 99%